2019
DOI: 10.1038/s41586-019-1814-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental ROS individualizes organismal stress resistance and lifespan

Abstract: A central aspect of aging research concerns the question as to when individuality in lifespan arises 1. We have now discovered that a transient increase in reactive oxygen species (ROS), which occurs naturally during early development in a subpopulation of synchronized Caenorhabditis elegans, sets processes into motion that increase stress resistance, improve redox homeostasis and ultimately prolong lifespan in those animals. We find that these effects are linked to the global ROS-mediated decrease in developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 36 publications
6
152
0
1
Order By: Relevance
“…An indication of the need for subtlety in thinking about the relation of ROS to ageing and lifespan comes from the finding by Bazopoulou et al [ 307 ] that a transient (10 h) increase in ROS in early development of Caenorhabditis triggers epigenetic mechanisms that result in increased stress resistance and redox homeostasis that in turn result in life span extension, the mediating mechanism being global decreases in histone H3K4me3 levels. A biphasic response such as this, where low levels of a potentially damaging molecule which is toxic at higher doses triggers the upregulation of cellular defense mechanisms that are ultimately beneficial to life expectancy was termed mitohormesis by Tapia [ 308 ].…”
Section: Mitochondrial Mutations and The Oxidative Damage Theorymentioning
confidence: 99%
“…An indication of the need for subtlety in thinking about the relation of ROS to ageing and lifespan comes from the finding by Bazopoulou et al [ 307 ] that a transient (10 h) increase in ROS in early development of Caenorhabditis triggers epigenetic mechanisms that result in increased stress resistance and redox homeostasis that in turn result in life span extension, the mediating mechanism being global decreases in histone H3K4me3 levels. A biphasic response such as this, where low levels of a potentially damaging molecule which is toxic at higher doses triggers the upregulation of cellular defense mechanisms that are ultimately beneficial to life expectancy was termed mitohormesis by Tapia [ 308 ].…”
Section: Mitochondrial Mutations and The Oxidative Damage Theorymentioning
confidence: 99%
“…For example, Murphy's group [112] used mPEG to show that mitochondrial reactive species inactivate pyruvate dehydrogenase kinase 2. Recently, Jakob's group [113] demonstrated that histone methyltransferase oxidation, evidenced using mPEG, decreases methylation, which enables stochastic fluxes in developmental reactive species to regulate lifespan via an epigenetic switch. The utility of mPEG is, however, limited because the bulky PEG sterically impedes thiol labelling [98].…”
Section: Click Pegylationmentioning
confidence: 99%
“…to induce and regulate a complex signaling network between mitochondria, the nucleus (Quiros et al, 2016), other organelles, such as lysosomes (Ramachandran et al, 2019), and the cytosol (D'Amico et al, 2017), resulting in increased cell stress resistance that can improve health and extend lifespan. Of particular interest is the recent observation that early developmental transient redox stress in Caenorhabditis elegans could indeed modify the methylation state of the genome, and lead to increased stress resistance, improved redox homeostasis, and prolonged lifespan (Bazopoulou et al, 2019).…”
Section: Ros and Mitochondria In Aging Progressionmentioning
confidence: 99%